SERAT SULUK PAWESTRI SAMARIYAH: SEBUAH PENCARIAN TIRTAMARTA DALAM NUANSA KEJAWEN-KRISTIANI - Prabowo, Danu Priyo (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
Manuscripts of Javanese literary texts with a Christian nuance are difficultto obtain. Compared with the development of the Hindu, Buddhism, and Moslemtraditions in Javanese literary culture, that of the Christian tradition is stillrelatively new. Only a few Javanese literary texts with a Christian nuance areassumed to be currently in existence.The writer has in hand a manuscript containing a Javanese literary texttitled Serat Suluk Pawestri Samariyah. Written in the style of tembang macapat, itis to be sung aloud and, according to the year to be guessed from the four-wordedJavanese phrase called a sengkalan there, it was written in 1853 in the Javanesecalendar or in 1921 A.D. and got into print as a book published in 1925 by A. C. Nix& Co., Bandung, telling about